Aspek Berkelanjutan : Faktor-Faktor Yang Mempengaruhi Pemberdayaan Kewirausahaan Karyawan Sebagai Mahasiswa S1 di Kabupaten Sidoarjo - Abdul Hafidz Rosydi Fuady; Didit Darmawan (Lembaga Pengembangan Kinerja Dosen, 2025)
Entrepreneurship in Sidoarjo Regency has experienced rapid development and has had a significant impact on regional economic growth. The government's role in providing support through various training programs, mentoring, and easy access to capital has encouraged the community, especially the younger generation, to engage in business activities. In higher education, entrepreneurship courses have a strategic objective, namely to shape and foster an entrepreneurial spirit in students so they are able to adapt, innovate, and achieve success in the future. As the number of students who also work as employees increases, it is important to understand the factors that can empower them in developing entrepreneurship. This study aims to analyze the influence of innovation behavior, entrepreneurial characteristics, entrepreneurial skills, business literacy, and social capital on the empowerment of entrepreneurs among undergraduate working students in Sidoarjo Regency. The research method used is quantitative with a survey approach. The research sample was selected using a purposive sampling technique, involving 200 working student respondents from various universities in Sidoarjo. Data collection was carried out through an online questionnaire that has been tested for validity and reliability. Data analysis used multiple linear regression to test the effect of each independent variable on the dependent variable. The results of the study indicate that innovation behavior, entrepreneurial characteristics, entrepreneurial skills, business literacy, and social capital significantly influence the entrepreneurial empowerment of working students, both partially and simultaneously. These findings indicate that the combination of personal abilities, technical skills, business knowledge, and strong social networks can be a determining factor in the success of working students in establishing and developing businesses. This research is expected to serve as a reference for universities and policymakers in designing more effective entrepreneurial empowerment programs that are relevant to the needs of working students.